2017
DOI: 10.1371/journal.pone.0176294
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with stage of change in smoker in relation to smoking cessation based on the Korean National Health and Nutrition Examination Survey II-V

Abstract: Despite a decrease in incidence, smoking remains the most serious public health problem worldwide. Identification of the factors contributing to changes in willingness to quit smoking may aid the development of strategies that encourage smoking cessation. Pooled cross-sectional data from 11,924 smokers from the Korean National Health and Nutrition Examination Survey II–V were analyzed. The stages of change in smoking cessation were categorized as pre-contemplation, contemplation, and preparation. Baseline char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…18) Another study reported that smokers with a higher educational level and income were more likely to consider quitting smoking within the next 6 months. 12) Most studies have consistently reported similar results. 10,13,18) However, in one study conducted in China, income was not significantly related to smoking cessation.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…18) Another study reported that smokers with a higher educational level and income were more likely to consider quitting smoking within the next 6 months. 12) Most studies have consistently reported similar results. 10,13,18) However, in one study conducted in China, income was not significantly related to smoking cessation.…”
Section: Discussionmentioning
confidence: 85%
“…Other studies have found that socioeconomic factors affect a person’s stage of smoking cessation [ 10 , 12 , 18 ]. In one study, socioeconomic status and change in the smoking cessation stage were found to be more relevant to male smokers than to female smokers [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As depression is not attributable to a small number of factors, trying to understand all of the potential causes can be a complex problem. For example, it has been widely shown that people who suffer from depression are more likely to engage in excessive smoking and drinking, creating a doubled-edged sword of harm towards one’s mental and physical health [ 4 ]. Further, trends in depression have been strongly linked to differences within gender [ 5 ], as well as socioeconomic and health-related reasons, such as obesity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%